APPLICATION OF AUTOLOGOUS SERUM EYE DROPS AFTER PTERYGIUM SURGERY: Autologous Serum Eye Drops - Rathore, Hassan Sajjad; Mukhtar, Ahsan; Saeed, Shahzad; Ijaz, Umar; Javaid, Mamoona; Ghaus, Iqra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the corneal epithelium healing time and post-operative pain after pterygium surgery with and without he use of autologous serum drops. Study Design: Comparative cross-sectional study. Place and Duration of Study: Eye Department, Combined Military Hospital Quetta, from Jan to Aug 2019. Methodology: Twenty patients were included in this study and divided into two groups. All patients underwent pterygium excision with conjunctival autograft. Fourteen of them were instilled with autologous serum drops while 14 were given lubricants postoperatively until corneal epithelium healed completely. Corneal epithelium healing time, visual analog scale for postoperative pain assessment, conjunctival inflammation and recurrences were evaluated. Patients were followed up for 6 months. Results: For corneal epithelial healing, 1 (7.14%) patient showed complete healing on day 2 while 7 (50%) showed healing on day 3 and 6 (42.86%) on day 4. While in non-autologous serum drops group 7 (50%) showed complete healing on day 4 while 4 (28.57%) showed healing on day 5 and 3 (21.43%) on day 6. The mean corneal healing time of autologous serum drops group was 3.36 ± 0.63 days and that of non-autologous serum drops group was 4.71 ± 0.83 days. Patients of autologous serum drops group also experienced significantly less pain as compared to the non-autologous serum drops group. While the recurrence rate and conjunctival inflammation in the two groups was found to be of equal degree. Conclusion: Patients who used autologous serum eye drops post operatively experienced less pain and their corneal epithelium healed earlier than the.......